Semiotic Analysis on TV Series Industry: Case Study of Criminal Minds Poster - Linuwih, Endar Rachmawaty; Harijanto, Shelvie; Fadilah, Eka (Universitas Tidar, 2024)
This research aims to identify and explain the signifiers, signified, denotations, connotations meanings, and myths embedded in the signs of the TV series Criminal Minds poster. In this research, the authors used the descriptive qualitative method to identify, analyze, and explain the signs in the Criminal Minds TV series poster. The authors also employ Ferdinand de Saussure and Roland Barthes' semiotic approach in the research. The primary data of this research is taken from both the verbal and nonverbal signs in Criminal Minds TV Series posters. This research shows that there are nine nonverbal and two verbal signs. Furthermore, after analyzing all of the signs (both verbal and nonverbal) in Saussure and Barthes' semiotic approach, this study found that all of the signs carry specific messages. Its purpose is to give the audience teasers or clues about the story, which tells about the journey of all main characters of Criminal Minds. Moreover, the myth commonly found across the signs in this TV series poster is to attract more potential viewers to watch the series.